Diagnóstico da situação dos resíduos da construção civil na cidade de São Carlos - SP - Röhm, Daniel Gobato (2013)
This work intends to present a diagnosis of the current situation of waste management for construction (RCC) on construction sites of construction companies operating in the city of São Carlos, SP, Brazil. For this methodology were applied as questionnaires and interviews with construction companies to the city, with views fetch results related to the stage of implementation of the management of RCC proposal by Brazilian resolution nº. 307 of the National Environment Council. Also data were collected for analysis in the municipal government sector generator. In this paper we present the results of analysis of perception of construction companies studied in relation to the management of RCC in their worksites and scaling parameter generation of RCC by licensed areas for new buildings along the City of Sao Carlos. For this parameter was concluded that San Carlos passed between the years 2009 and 2012, 2,347,694.93 m² of new construction, which reflects tremendous growth of construction in the city over the past four years. However, this table expansion was not accompanied by efficient management of waste produced in the beds, which can be seen by the increase in annual generation from 63,877.76 tonnes in 2009 to 82,413.38 tonnes in 2012.